PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA WANITA USIA SUBUR DALAM DETEKSI DINI KANKER PAYUDARA DI WILAYAH KERJA PUSKESMAS TAMBANG - Yadriati Maya Pesa (Jurnal Kesehatan Husada Gemilang, 2019)
Breast cancer is a tumor that grows in breast tissue. SBE is an effort to detect breast cancer early by examining the breast. Data from RSUD of Arifin Achmad Pekanbaru, breast cancer increased from 31.9% in 2013 becomes 50.5% in 2014. 90% of breast cancers were discovered by the women their selves through the SBE. It reduces up to 20% the rate of death from breast cancer.Those who practice SBE are 25%-30%. The research aims at identifying the factors related to SBE behavior such as knowledge, attitudes, motivation, information media, family support, and role of health workers and education. This is an observational analytical quantitative research with a cross sectionaldesign. The data were analyzed through the univariate, bivariate with chi square test, and multivariate with double logistic regression. Finally, it is initiated that knowledge of is at OR 5,090 (C.I 95%: 1,677-15,453) and motivation is at OR 11,402 (C.I 95%: 1,418-91,682), and confounding variables are attitudes towards knowledge and motivation. Unrelated variables are the role of health workers, information media, family support and education. Accordingly, there is a causal correlation among knowledge, motivation, and SBE behavior in eligible women. So, it is suggested that they are to consult with health personnel about SBE and health workers provide counseling and guidance about it so that they have good knowledge and want to practice it.